Strategic Communication Management: Crafting a Positive Image for Madrasah Excellence - Naufal Fahmi Habibullah Naufal; Uswatun Hasanah; Laila Fakhriyatus Zakiyah (Al-Qalam Institue, 2023)
This research aims to determine the management of communication strategies in building the image of madrasas and changing the public's perspective towards MTs Miftahul Ulum Krejengan Probolinggo. The analysis uses a qualitative approach of case study type. This research focuses on communication strategies in building a madrasah sutra at MTs Miftahul Ulum Krejengan Probolinggo. The selection of a qualitative approach aims to understand communication strategies in building the image of madrasas at MTs Miftahul Ulum Krejengan Probolinggo. The case study was chosen to focus on the case under study. The research results show that MTs Miftahul Ulum carries out two communication management, namely internal communication management and external communication management. MTs Miftahul's internal communication management has an essential impact on creating a solid organization, using personal and group communication. Communication management is also carried out to solve organizational conflicts or problems. External communication management is carried out by MTs Miftahul to maintain organizational relationships with external parties and build the image of MTs Miftahul. Relations with the government, banking, press, consumers, surrounding community, and other organizations. This research provides implications regarding the importance of educational institutions in maintaining the image of madrasas by implementing communication strategies that impact image-building and changing society's perspective.